Cultural Acculturation and Wasathiyyah Islamic Values in Celebrating the Ruwatan Ceremony in Kelud Mountain - Ismi Rohmattul Muslimah (International Journal of Religion and Social Community, 2024)
The purpose of this article is to identify the Wasathiyyah Islamic values that appear in the practice of ruwatan ceremonies and how these values influence the behaviour of the community, especially in Mount Kelud. Ruwatan ceremony is a tradition aimed at cleansing oneself from negative influences that people believe in eliminating diseases, bad luck and even natural disasters. This research uses qualitative research with cultural anthropology and theological approaches that can be understood in the context of Islamic teachings. Data collection techniques through interviews, observation and documentation using triangulation analysis and data presentation. Ruwatan is not just a tradition but also a place to implement the teachings of Islam in a wasathiyyah manner, which emphasises moderation and balance between communities on Mount Kelud.